Modelo de gestão de predição de falhas no gerenciamento da infraestrutura de datacenter - Santos, Reginaldo Hugo Szezupior dos [UNESP] (2014)
This paper proposes a management model for predicting failures in Datacenter infrastructure management, based on the good practices for managing IT (Information Technology) infrastructure. The model refers to a system that monitors the Datacenter and detects faults in legacy equipment, thereby, avoiding that they collapse. Based on the ITIL library, but focusing only on the most relevant modules to the work objectives, the model was implemented and used to monitor legacy equipment for a particular Datacenter, allowing the information storage that could be collected remotely and used to prevent problems involved with the monitored data. The practical system, obtained from the model is composed of three (3) basic devices: End Device, Device Rack and Power Device. The results show that the system is feasible and can be applied effectively in actual applications